Pengaruh Kurs Terhadap Pengangguran, Utang Luar Negeri, Neraca Perdagangan, Dan Pertumbuhan Ekonomi Di Indonesia - Clemment Marvello Fedihartono; Nerissa Arcellya Virjannah; Muhammad Yasin (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study analyzes the effect of exchange rates on unemployment, foreign debt, trade balance, and economic growth using time series. Data sourced from the website of the Central Bureau of Statistics, the Ministry of Finance of the Republic of Indonesia, and Bank Indonesia. The results showed that the exchange rate did not affect the unemployment rate before the 1997 economic crisis but after the economic crisis the exchange rate had a positive effect, while on foreign debt it showed that the rupiah exchange rate had a positive and significant effect. In addition, the rupiah exchange rate had a positive effect on Indonesian trade merchandise in 1980-2012 and the results of the F test found that simultaneously the exchange rate had a significant effect on economic growth.